US-Fantasy 1977-1987 Eine Genrebetrachtung - Haupts, Tobias (Cinepoetics Essay, 2022)
At the end of the 1970s, a new genre cycle was formed in US cinema. Starting with space opera in cinema, for which George Lucas' Star Wars is paradigmatic, fantasy established itself for the first time as an independent cinematic genre in distinction from fairy tales and fantastic fiction. The enthusiasm for pen & paper role-playing games and the continuing J. R. R. Tolkien craze culminated in the following years in a series of films that absorbed, pushed and further developed the diversity of modern film technology and production: the spectrum of films ranged from live-action films (Conan the Barbarian) to puppet animation (The Dark Crystal) to animated films (The Last Unicorn), in which George Lucas as well as Jim Henson and the production companies behind them at the time played leading roles. Contemporary critics had written these films off as conservative, sometimes even reactionary genre plays. In contrast, this essay unfolds a (historical) poetics of the US fantasy film. With its film-analytical case studies, the volume shows how the films of the years 1977 to 1987 are embedded in a specific film culture and how the genre cycle as part of the Hollywood system prepared and significantly influenced the triumph of blockbuster cinema in the 1990s.